Gender Differentials in the Awareness of Lassa Fever and Preventive Measures among Inhabitants of Enugu North Local Government Area, Enugu State - Opeyemi, Bolaji; Oluwafemi, Joshua; Enyi, Catherine Nkeiru; Odoh, Chidimma Lucy (International Journal of Human Kinetics, Health and Education, 2023)
The study investigated gender differentials in the awareness of Lassa fever and preventive measures of Lassa fever among inhabitants of Enugu North (LGA). The study adopted the descriptive cross-sectional survey research design. The population for the study consisted of all inhabitants of Enugu North LGA which total was 154,808. The sample size for the study was 450 inhabitants of Enugu North LGA using simple sampling technique of balloting without replacement. The instrument for data collection was Gender Differentials Awareness of Preventive Measures of Lassa Fever Questionnaire. The split -half method, through spearman Brown coefficient was used to test for reliability of the instrument,. Frequencies and percentages were used to answer the research questions, while Chi-square statistics was used to test hypotheses. Results indicated that male inhabitants possessed high level of awareness of mode of transmission of Lassa fever (73.93%) as well as moderate levels of signs and symptoms (57.79%), and preventive measures (69.93%), while female inhabitants possessed a moderate level of mode of transmission of Lassa fever (55.11%), signs and symptoms (54.84%), and preventive measures (62.02%) of Lassa fever. Also, Chi-square tests indicated no significant difference in the awareness of Lassa fever and its preventive measures based on gender. Based on the findings it was recommended that regular maintenance of personal hygiene and environmental practices should be encouraged in order to sustain the existing awareness of Lassa fever in the community.